Antihypertensive Medication Postpones the Onset of Glaucoma: Evidence From a Nationwide Study. Issue 2 (February 2017) - Horwitz, Anna; Klemp, Marc; Jeppesen, Jørgen; Tsai, James C.; Torp-Pedersen, Christian; Kolko, Miriam
Abstract : The aim was to investigate the impact of antihypertensive medication on the onset of glaucoma. Data from the complete Danish population between 40 and 95 years of age were used in the period from 1996 to 2012, covering >2.6 million individuals. The National Danish Registry of Medicinal Products Statistics was used to identify all claimed prescriptions for glaucoma medication and antihypertensive drugs. We first investigated basic correlations in the data and found that patients treated with antihypertensive medication, at any time during the study period, had a significantly higher overall relative risk (RR) of glaucoma, even when controlling for age and sex (with a RR of 1.31 and P <0.0001). Furthermore, our data confirm the well-known positive association between age and glaucoma. To investigate the causal effect of antihypertensive treatment on the onset of treatment for glaucoma, we used a regression discontinuity study design. This analysis provides our main finding, namely that prescription of antihypertensive medication leads to a significant reduction in the risk of developing glaucoma. Therefore, although hypertension—as indicated by the use of antihypertensive medication—is positively correlated with glaucoma, our study indicates that antihypertensive medication itself may have a preventive effect on the development of glaucoma. Abstract : Supplemental Digital Content is available in the text.